ECDomainMiner: discovering hidden associations between enzyme commission numbers and Pfam domains. Issue 1 (December 2017) - Alborzi, Seyed; Devignes, Marie-Dominique; Ritchie, David W.
Abstract Background Many entries in the protein data bank (PDB) are annotated to show their component protein domains according to the Pfam classification, as well as their biological function through the enzyme commission (EC) numbering scheme. However, despite the fact that the biological activity of many proteins often arises from specific domain-domain and domain-ligand interactions, current on-line resources rarely provide a direct mapping from structure to function at the domain level. Since the PDB now contains many tens of thousands of protein chains, and since protein sequence databases can dwarf such numbers by orders of magnitude, there is a pressing need to develop automatic structure-function annotation tools which can operate at the domain level. Results This article presents ECDomainMiner, a novel content-based filtering approach to automatically infer associations between EC numbers and Pfam domains. ECDomainMiner finds a total of 20, 728 non-redundant EC-Pfam associations with a F-measure of 0.95 with respect to a "Gold Standard" test set extracted from InterPro. Compared to the 1515 manually curated EC-Pfam associations in InterPro, ECDomainMiner infers a 13-fold increase in the number of EC-Pfam associations. Conclusion These EC-Pfam associations could be used to annotate some 58, 722 protein chains in the PDB which currently lack any EC annotation. The ECDomainMiner database is publicly available athttp://ecdm.loria.fr/ .